The Estimation of Cementoenamel Junction Crestal Bone Distance in Mandibular Anterior Teeth - Ahmed AS; Ali BJ; Hassan BK; Sabah Mohammad A (Clinical, Cosmetic and Investigational Dentistry)
Ammar Sh Ahmed,1 Banaz Jabbar Ali,2 Ban Karem Hassan,2 Abbas Sabah Mohammad3 1Department of Pedodontics, Orthodontic and Preventive Dentistry, College of Dentistry, Mustansiriyah University, Baghdad, Iraq; 2Department of Periodontics, College of Dentistry, Mustansiriyah University, Baghdad, Iraq; 3Al-Sabah Center, Al- Yarmouk, Baghdad, IraqCorrespondence: Ban Karem Hassan, College of Dentistry, Mustansiriyah University, 6 street Al Mustansiriya, Baghdad, 10052, Iraq, Tel +9647901468790, Email ban.k.hassan@uomustansiriyah.edu.iq, ban_karem_2006@yahoo.comPurpose: The study aimed to measure the distance from the cementoenamel junction (CEJ) to the alveolar bone crest on both the buccal and lingual sides of the anterior mandibular teeth utilizing cone beam computed tomography (CBCT).Materials and Methods: Cone-beam computed tomography (CBCT) was utilized to measure the distance between CEJ and the alveolar bone crest on both the buccal and lingual sides of the mandible’s anterior teeth.Results: The mean of the distance on buccal side for the central, lateral, and canine teeth were (1.6 mm), (1.6 mm), and (1.5 mm) respectively. On the lingual side, the mean for all teeth (central, lateral, and canine) was 1.7 mm. The study demonstrated a significant difference in distance across age groups (< 30 and ≥ 30 years) for all teeth on both the buccal and lingual sides, except for the canine on the buccal side.Conclusion: The distance from the CEJ to the bone crest on both the buccal and lingual sides varies significantly by age group. This data is essential for developing orthodontic, implant, and periodontal therapies.Keywords: alveolar bone crest, canines, cementoenamel junction, central incisors, cone-beam computed tomography, lateral incisors